Exposure to a 50 Hz magnetic field at 100 µT exerts no DNA damage in cardiomyocytes - Yong Wang; Xingfa Liu; Yemao Zhang; Baoquan Wan; Jiangong Zhang; Wei He; Dong Hu; Yong Yang; Jinsheng Lai; Mengying He; Chen Chen (Biology Open, 2019)
The effects of exposure to magnetic fields (MFs) at electric frequencies (50–60 Hz) on carcinogenicity are still in debate. Whether exposure to MFs affects the heart is also a debated issue. This study aimed to determine whether exposure to extremely low frequency MFs (ELF-MFs) induced DNA damage in cardiomyocytes both in vitro and in vivo. Human ventricular cardiomyocytes were exposed to 50 Hz ELF-MF at 100 µT for 1 h continuously or 75 min intermittently. The effects of the treatments were evaluated by DNA damage, redox status changes and relative signal molecular expression. Moreover, ten male Sprague-Dawley rats were exposed to a 50 Hz MF at 100 µT for 7 days, while another 10 rats were sham exposed. The protein levels of p53 and Hsp70 in heart tissue were analyzed by western blot. The results showed that exposure to ELF-MF did not induce DNA damage, changes to cell cycle distribution or increased reactive oxygen species level. No significant differences were detected in p53 and Hsp70 expression level between the ELF-MF and sham-exposure groups both in vitro and in vivo. All these data indicate that MFs at power-frequency may not cause DNA damage in cardiomyocytes. This article has an associated First Person interview with the first author of the paper.